TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN ATAS IKLAN PRODUK KOSMETIK YANG MENYESATKAN - SAFITRI, PUTRI UTAMI DIAN (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
Business development of a product or service requires a means to inform a product so that consumers know the quality of the product so that they are interested in buying it. The means in question are advertisements or advertisements that have a function as part of a marketing strategy, so that every advertisement is always made in such a way that it can attract the attention of consumers because it has the potential to cause misleading advertisements by showing the efficacy of a product through excessive depiction using television media. resulting in an impressive display effect. The number of cosmetic advertisements currently circulating in the mass media, many of which are not objective, incomplete, and can be misleading. Misleading information on goods and services through advertisements not only has the potential to harm consumers materially but can even further endanger the health and life of consumers, as well as eliminate consumer confidence in the information submitted by business actors. Therefore, consumers have the right to seek legal protection against the delivery of such misleading advertisements.